The 10-minute consultation. - Aldegather, Jehad (10-minute consultation., 2006)
A concise pocket guide outlining the increasing prevalence of risk factors for cardiovascular disease and therefore the need for primary care clinicians (GPs, nurses and pharmacists) to correctly identify and manage them, with practical information on how to carry out the necessary tests, examinations and investigations within the standard '10-minute' consultation framework.